ANÁLISIS DEL RIESGO CREDITICIO Y SU INCIDENCIA EN EL NIVEL DE MOROSIDAD DE LA FUNDACIÓN DE DESARROLLO COMUNITARIO SIN FRONTERAS, “DECOF”, AGENCIA LOJA PERIODO 2017-2018 - Paccha Benitez, Gina Alexandra (2019)
He presents work entitled: "ANALYSIS OF CREDIT RISK AND ITS INCIDENCE IN THE LEVEL OF DEFAULT OF THE COMMUNITY DEVELOPMENT FOUNDATION WITHOUT BORDERS," DECOF ", AGENCY LOJA PERIOD 2017-2018" allowed obtaining a diagnosis on the real state of the Foundation through the analysis made to the financial statements was able to know the economic and financial position of the years 2017-2018, and establish a credit risk rating parameter present in the financial intermediation processes. This thesis begins with the analysis of the structure of the microcredit portfolio, where it was possible to know the critical knots of the management of financial intermediation; for which the indicators established by the SEPS were applied, in order to be aware of the variations that were presented during the periods that were analyzed and the accounts that make up the working capital to determine the use of the resources required by the foundation to its operation; Subsequently, information was collected on the procedures for granting the loans and the policies of the foundation, with the purpose of verifying compliance with the processes for the location of the credits, the main activity of the foundation, obtaining through from it a profitability the same 5 as for its structure and mission must be reinvested in the location of new credits, so it is necessary a correct analysis and takes necessary measures to avoid and reduce the existing delinquency. We proceeded to apply the credit rating method of Credit 5 C credits complemented with the Scoring that allowed to grade the level of irrigation to which the foundation is exposed It was concluded with the preparation of the report which contains the results obtained from the analysis made to the financial statements and the application of the credit risk rating method, as well as conclusions and recommendations that contribute to the managers to make decisions focused on the improvement of the activities of the foundation.